Kualitas Pelayanan dan Tingkat Kepuasan Anggota Koperasi Unit Desa Suraberata Kecamatan Selemadeg Bara - Eliyawati, Wayan; Sutjipta, Nyoman; Putra, Setiawan Adi (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 4 No 1 (2016), 2016)
A cooperative or an economic enterprise is a coordinating institution of the economic democracy development with the aim to gather the development potention in order to be able to increase the standard and the prosperity of the society. A cooperative needs to follow any strategic steps to continue competing and keep up the exsistance by increasing the quality of human resource and service with the result that the members can feel themselves valuable, satisfied, concerned, or have a good and respectable attention. A care service is a strategy in winning the competition. One other way to raise customer satisfaction is by increasing the quality of service. The purpose of this study is to analyze the quality of service and the level satisfaction of members of the Suraberata village unit of cooperative in West Selemadeg Subdistrict. The method of this research is deskriptif kualitatif method. The sample on the population was conducted by using Slovin Formula. It was taken  in proportional random sampling which concerned on 96 respondents which are the members of the cooperative from the 12 vilages in West Selemadeg Subdisctrict. The techniques of analyzing data were Servqual Quality Analysis and Importance Performance Satisfaction Analysis.   The result of Servqual quality analysis showed the average numbers of the the quality of service expected by the members was 4, 27, meanwhile the average numbers of the fact of service accepted was 3, 29. There was a gap occurred cohesively from the five indicators of the accepted quality of service with the expected quality of service for 0, 35. The result of Importance – Performance showed that the indicator level categories “Very Satisfied” is the physical evidence indicator. The Indicators with category level “Quite Satisfied”are reliability indicator and assurance indicator. The indicator for level “Unsatisfied” was the response indicator and emphatic indicator. From the result of this study can be concluded that Suraberata Village unit was not able to give the first-rate quality of sercive to the members of the cooperative. The cooperatvive was able to give the “very satisfied” level of satisfaction on the service of physical facility performance, “quite satisfied”level for knowledge, attitude, and dependable action in giving service, and “unsatisfied” level in personal caring, understand the demands of the members, the willing to assist the members, giving quick and perceptive service. The suggestion of this study is to increase the quality of service from Suraberata village unit of cooperative to raise the satisfaction of the members.
Keywords: The quality of service, the satisfaction of members